NLP : an introductory guide to the art and science of excellence - Harris, Carol (Element, 1999)
Neuro-Linguistic Programming (NLP) is becoming widely recognized as a powerful, holistic set of approaches and techniques to enable everyone to achieve results. This text shows how Neuro-Linguistic Programming (NLP) can be used for the whole life - from how to think, feel and act in business life to social, emotional, mental, physical and spiritual life.